Screening for juvenile idiopathic arthritis associated uveitis with laser flare photometry in the pediatric rheumatology office: a prospective observational study - Kaleo Ede; Michael Shishov; Elisa Wershba; Nikita Goswami; Sabrina Gorry; Malin Joseph; Lucia Mirea; James O'Neil (BMC, 2024)
Abstract Background Juvenile Idiopathic Arthritis (JIA) Associated Uveitis (JIA-U) remains one of the most serious complications of JIA in children. Historically, pediatric JIA is diagnosed by an Optometrist or Ophthalmologist; however, barriers to scheduling increase wait times that may delay diagnosis and treatment. The purpose of this study was to evaluate laser flare photometry (LFP) use to diagnose JIA-U in the Pediatric Rheumatology clinic for patients with JIA. Methods This prospective, observational study assessed pediatric patients diagnosed with JIA without a previous history of uveitis between January 2020 and September 2022. All patients underwent at least one evaluation of both eyes using a Kowa FM-600 laser flare photometer during a routine Rheumatology appointment, as well as a standard slit lamp examination (SLE) by optometry or ophthalmology during routine clinical care. Data collected at patient visits included demographics, JIA characteristics, treatment, LFP readings, and anterior chamber (AC) cell grade score utilizing the SUN grading system. Data were summarized using descriptive analyses and the uveitis false positive rate was calculated. Results The study cohort included 58 pediatric patients diagnosed with JIA. The mean age was 8.4 years (1.2-16.3 years) at diagnosis and 11.9 (4.8-16.5 years) at enrollment. The mean duration of disease at time of enrollment was 42 months (range; 0-157 months). Participants were predominantly female (n = 43, 74.1%) and white/Caucasian race (n = 37, 63.8%). The most common JIA subtypes included persistent oligoarticular JIA (n = 19, 32.8%), and RF negative polyarticular JIA (n = 12, 20.7%). There were 12 ANA positive patients (20.7%). At enrollment, 16 patients (27.6%) were not on medications, with 20 (34.5%) on methotrexate, 20 (34.5%) on adalimumab, 6 (10.3%) on tocilizumab, and 5 (8.6%) on etanercept. During the study period, no eye exams detected active uveitis based on SLE with a SUN grade over 0. However, of the 135 LFP readings, 131 (97.0%) were normal, yielding a false positive rate of 3% (95% CI: 0.8%, 7.4%). Conclusions LFP is a non-invasive tool that can be utilized in the pediatric rheumatology clinic to evaluate for JIA-U. There is a low false positive rate of LFP when compared with standard slit lamp exam.